2005
DOI: 10.1542/peds.2004-2671
|View full text |Cite
|
Sign up to set email alerts
|

Initial Neurologic Presentation in Young Children Sustaining Inflicted and Unintentional Fatal Head Injuries

Abstract: ABSTRACT. Background. It remains unclear if fatal brain injuries in young children are characterized by immediate rapid deterioration or can present after an initial period of lucidity. This issue has legal implications in child abuse, for which understanding the clinical course affects perpetrator identification.Objective. To determine patterns of neurologic presentation on hospital admission in infants and toddlers who die of inflicted and unintentional injury.Design/Methods. Data on children <48 months of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Whereas axonal tearing results in immediate loss of function and a lucid interval is unlikely, brain swelling takes place with a speed and severity of huge individual variation, which may allow a lucid interval or a period in which cerebral function is gradually impaired. 25,26 This is particularly likely to occur in infants whose skulls still have unfused sutures, and are, therefore, distensible. 27 The alternative hypothesis Geddes had observed that infants with NAHI commonly have a thin bilateral film of subdural blood, sometimes so small that it is missed on scans.…”
Section: Biomechanicsmentioning
confidence: 99%
“…Whereas axonal tearing results in immediate loss of function and a lucid interval is unlikely, brain swelling takes place with a speed and severity of huge individual variation, which may allow a lucid interval or a period in which cerebral function is gradually impaired. 25,26 This is particularly likely to occur in infants whose skulls still have unfused sutures, and are, therefore, distensible. 27 The alternative hypothesis Geddes had observed that infants with NAHI commonly have a thin bilateral film of subdural blood, sometimes so small that it is missed on scans.…”
Section: Biomechanicsmentioning
confidence: 99%
“…8 Detailed studies of unintentional injuries among infants have focused largely on specific products (eg, bathtub seats, 9 strollers/shopping carts, 10,11 infant carriers, 12 or high chairs 13 ). Other work has focused on a particular cause of injury (eg, falls 14 or burns 15 ) or a particular diagnosis (eg, head injuries 16,17 ).…”
mentioning
confidence: 99%
“…The large majority of children had minor head trauma with asymptomatic presentation or with a history of only temporary loss of consciousness. This study emphasizes the practice that CT is rarely necessary in these children, but -and most importantly -only after careful clinical evaluation and a knowledge of the risk factors for intracranial injury [2,5,6,8].…”
mentioning
confidence: 86%